2012
DOI: 10.1007/s10995-012-1112-x
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Sociodemographic Risk Factors for Preterm Birth in a French Caribbean Population of African Descent

Abstract: There appears to be an incompressible high rate of preterm births among populations of African origin irrespective of their geographic location. The objective of this study was to assess the risk factors for preterm birth in a French Caribbean population of African descent, offered medical care comparable to that on the French mainland, but presenting a higher rate of preterm birth. The study was based on a birth cohort at maternity hospitals in Guadeloupe (French West Indies) including 911 singleton pregnanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…This is probably due to the persistence of the cause of the previous preterm delivery in such patients. This is in keeping with the findings of previous Nigerian studies 4,15,29 and Rouget 26 in France. Prelabour rupture of membranes was found to be a significant risk factor for preterm delivery from our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is probably due to the persistence of the cause of the previous preterm delivery in such patients. This is in keeping with the findings of previous Nigerian studies 4,15,29 and Rouget 26 in France. Prelabour rupture of membranes was found to be a significant risk factor for preterm delivery from our study.…”
Section: Discussionsupporting
confidence: 93%
“…4,6 We found a higher likelihood of preterm birth among women greater than 35 years. This finding is similar to the reports of Rouget et al 26 and Hoffman et al 27 who also found an association between the older pregnant woman and preterm birth. The relationship between advanced maternal age and preterm delivery is probably related to the higher likelihood of medical conditions that may necessitate early delivery among this age group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It covers an area of 1628 km 2 and has a population of 450 000 inhabitants. This study relies on the TIMOUN mother-child cohort fully described elsewhere 15. Briefly, between 2004 and 2007, 1068 women attending check-up visits at public hospitals or dispensaries during their third trimester of pregnancy and having resided in Guadeloupe for >3 years were enrolled in the cohort.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, desert dust natural pollution is the main factor affecting PM 10 concentrations. Second, a high rate of preterm birth (15.8%) is observed in Guadeloupe 15. This high preterm birth rate is not fully understood, but it could be partly due to the African origin of its population, which as such presents a refractory high rate, common to populations of African descent, irrespective of their current geographic location and independent of socioeconomic status and obstetrical care 16.…”
Section: Introductionmentioning
confidence: 99%